2022
DOI: 10.1002/advs.202202795
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Intensity Enhancement in Tin Halide Perovskites

Abstract: The prevalence of background hole doping in tin halide perovskites usually dominates their recombination dynamics. The addition of excess Sn halide source to the precursor solution is the most frequently used approach to reduce the hole doping and reveals photo‐carrier dynamics related to defects activity. This study presents an experimental and theoretical investigation on defects under light irradiation in tin halide perovskites by combining measurements of photoluminescence with first principles computation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…From CBC to CBB sample, the PL intensity decreases with the increase in the Br content since replacing smaller halide ions with larger ones can distort the crystal structure of the perovskite, which may lead to the formation of defects [35] . The presence of more defects on the photocatalyst can act as traps for the recombination, hindering the PL intensity of the photocatalysts [36] . In the case of combined Cl and Br perovskites, the PL intensity decreases with the Cl/Br ratio increase following the sequence x=0.9<0.8<0.7<0.6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From CBC to CBB sample, the PL intensity decreases with the increase in the Br content since replacing smaller halide ions with larger ones can distort the crystal structure of the perovskite, which may lead to the formation of defects [35] . The presence of more defects on the photocatalyst can act as traps for the recombination, hindering the PL intensity of the photocatalysts [36] . In the case of combined Cl and Br perovskites, the PL intensity decreases with the Cl/Br ratio increase following the sequence x=0.9<0.8<0.7<0.6.…”
Section: Resultsmentioning
confidence: 99%
“…[35] The presence of more defects on the photocatalyst can act as traps for the recombination, hindering the PL intensity of the photocatalysts. [36] In the case of combined Cl and Br perovskites, the PL intensity decreases with the Cl/Br ratio increase following the sequence x = 0.9 < 0.8 < 0.7 < 0.6. J. Yan et al showed that Cl À and Br À ions can either inhibit or promote the formation of clusters and modify the PL intensity.…”
Section: Optical Propertiesmentioning
confidence: 95%
“…The enhancement of photocatalytic performance relies on the efficient segregation of photogenerated electron–hole pairs . The electron–hole separation efficiency of the catalyst was evaluated through a combination of electrochemical properties and photoluminescence characteristics . As shown in Figure a, of all of the ZnSe/Ag 2 Se catalyst series, 15% ZA exhibits the highest transient photocurrent intensity.…”
Section: Resultsmentioning
confidence: 99%
“…55 The electron−hole separation efficiency of the catalyst was evaluated through a combination of electrochemical properties and photoluminescence characteristics. 56 As shown in Figure 9a, of all of the ZnSe/Ag 2 Se catalyst series, 15% ZA exhibits the highest transient photocurrent intensity. This observation is further reinforced by the electrochemical impedance spectroscopy (EIS) results, as illustrated in Figure 9b.…”
Section: Mechanisms Of Enhanced Photocatalytic Efficiencymentioning
confidence: 90%
“…Figure illustrates the PL spectra of the samples before and after exposure to ambient air. After the exposure, a degradation of PL intensity was observed owing to the formation of nonradiative recombination centers resulting from the oxidative degradation. Samples with higher impurity ratios after the exposure exhibited lower PL intensities. The PVK-NaI series demonstrated less degradation in PL intensities compared with the other samples.…”
Section: Resultsmentioning
confidence: 99%